2021
DOI: 10.1016/j.msard.2021.103028
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the COVID-19 AstraZeneca vaccination in people with multiple sclerosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
2
17
0
4
Order By: Relevance
“…Most studies (33/34) included patients vaccinated with the BNT162b2 (Pfizer, n = 33) or the m-1372 (Moderna, n = 12) mRNA vaccines. Only 731 patients receiving recombinant adenoviral vector vaccines ( n = 711 ChAdOx1-nCoV-19, Astrazeneca, n = 20 Ad26.COV2.S, Janssen) and 51 receiving inactivated virus vaccines (BBV152, Bharat) have been described in 7/34 studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. One study reported disaggregated safety data by vaccine type, although limited to the first half of the vaccination cycle [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies (33/34) included patients vaccinated with the BNT162b2 (Pfizer, n = 33) or the m-1372 (Moderna, n = 12) mRNA vaccines. Only 731 patients receiving recombinant adenoviral vector vaccines ( n = 711 ChAdOx1-nCoV-19, Astrazeneca, n = 20 Ad26.COV2.S, Janssen) and 51 receiving inactivated virus vaccines (BBV152, Bharat) have been described in 7/34 studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. One study reported disaggregated safety data by vaccine type, although limited to the first half of the vaccination cycle [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most patients had an established diagnosis with relatively long follow-up data. Five of seven studies where disease duration was reported, included patients living with an autoimmune disorder for an average timespan of 10–15 years [ 33 , 51 , 57 , 60 , 61 , 63 ]. In 12 out of 24 studies with available data (57%), the average patient age ranged between 40 and 55 years.…”
Section: Autoimmune/rheumatic Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Eine interviewbasierte Untersuchung von MS-Erkrankten aus Großbritannien fand keine neuen Sicherheitssignale nach Vakzinierung mit dem vektorbasierten ChAdOx1nCoV-19-Impfstoff von Astra Zeneca ( n = 29) und dem BNT162b2-COVID-19 mRNA-Impfstoff von BioNTech/Pfizer ( n = 4) [ 35 ]. Acht der befragten Personen wurden mit Cladribin-Tabletten behandelt.…”
Section: Sars-cov-2-impfung Bei Personen Mit Ms Unter Behandlung Mit Cladribin-tablettenunclassified